Effects of News Commercialisation on News Credibility in Cameroon: A Survey of Journalists and Audience - Ngange, Kingsley L.; Enjema, Stone Mira; Ndode, Stephen N. (Journal of Media, Journalism & Mass Communication, 2026)
News commercialisation is geometrically increasing in the Cameroon media landscape. Its rise dampens journalists’ credibility because it is inextricably linked to media corruption, control, and unethical practices. Accountability and transparency - key factors of media performance and credibility - cannot be guaranteed. This research examines the implications of this worrying phenomenon on new credibility in Buea, Cameroon. The study is anchored on Social Responsibility and Framing theories. Data were collected from 73 respondents out of 97 sampled (75.3%) and 384 media audiences in the metropolis to respond to the two research questions: to what extent does poverty influence the practice of news commercialisation? and by how much does news commercialisation affect news credibility? The journalists assert that news commercialisation is largely due to various forms of poverty: situational (80.8%), absolute (79.5%), rural (61.7%), psychological (61.6%) and generational (58.9%). Parametric analysis confirms that poverty significantly influences (t (df = 72) = 17.6, p < .05 (p=0.000) news commercialisation. Journalists admitted that they engage in this corrupt practice due to low remuneration, a lack of professional training, pressure from donors, peer pressure, greed, poor working conditions, and a lack of understanding of journalism ethics. This corrupt practice significantly (p=0.000) affects audience perception of news credibility and the canons of journalism (accuracy, objectivity, balance, and impartiality). The study beckons media owners to improve working conditions of journalists, especially their wages. This could contribute to ameliorating journalists’ financial situation and limit their involvement in commercialising news.